The New Brachylogy as Thinking Fictions in the Writings of Abdelfattah Kilito: The Case of The Arabs and the Art of Storytelling: A Strange Familiarity and The Tongue of Adam - Nouamane JADOUAL; Mounir SERHANI (International Journal of Scientific Research and Innovative Studies, 2025)
Abdelfattah Kilito’s writings explore the possible interactions between the movement of thought and fictional experience. This new conception of contemporary narrative is not limited to a simple hybridization of literary genres but represents a new way of combining narrative invention and critical reflection. Beyond this intermingling of forms, the question raised is deeply delicate, involving literary, rhetorical, biographical, socio-historical, anthropological, and psychoanalytic aspects. Kilito, who is reticent about intellectual labels, undertakes an exploration of the origins of thought, highlighting an ancient paradigm that touches on the reinterpretation of the literary text through fragmentary thoughts and meaningful images. This article aims to highlight the notion of laconic discourse and speaking silence, which, in Abdelfattah Kilito’s work, fuels both his fictions and his reflections. For the writer, language becomes the allegory of thought, the very terrain on which it unfolds, through a reading grid dominated by a multiplicity of interpretations. Kilito uses words to solicit an experience of thought, one from which emerges an emotion of life or reflection that eludes him. The discourse is transformed into a string of condensed ideas, called brachylogical, whose characteristics this analysis explores. Keywords: Fiction, brachylogy, reflection, fragmentation, essay. Received Date: July 20, 2025 Accepted Date: August 12, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/415